2022
DOI: 10.1039/d2bm01130a
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial poly(ionic liquid)-induced bacterial nanotube formation and drug-resistance spread

Abstract: Bacterial nanotubes are tubular membranous structures bulging from cell surface that can connect neighboring bacteria for the exchange of intercellular substances. However, little is known about the formation and function...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…To evaluate the PIL‐P‐Ce' role in preventing bacterial drug resistance spread, two E. coli strains with different ARGs and fluorescent genes were used for transformation experiments. [ 30 ] Plasmid solution from BL21 (carrying green GFP and Kan R genes) was incubated with the PIL‐P‐based membranes under 30 min of light, then mixed with DH5α (plasmid carrying red mCherry and Amp R genes) for transformation, followed by antibiotic screening, PCR, and fluorescence assays (Figure 3F ). Photos show that pristine DH5α can grow on the Amp plate, forming red colonies, while transformed bacteria could survive on the plate with both Amp and Kan, turning into white colonies after acquiring the BL21 strain's plasmid (Figure 3G ; Figure S12 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the PIL‐P‐Ce' role in preventing bacterial drug resistance spread, two E. coli strains with different ARGs and fluorescent genes were used for transformation experiments. [ 30 ] Plasmid solution from BL21 (carrying green GFP and Kan R genes) was incubated with the PIL‐P‐based membranes under 30 min of light, then mixed with DH5α (plasmid carrying red mCherry and Amp R genes) for transformation, followed by antibiotic screening, PCR, and fluorescence assays (Figure 3F ). Photos show that pristine DH5α can grow on the Amp plate, forming red colonies, while transformed bacteria could survive on the plate with both Amp and Kan, turning into white colonies after acquiring the BL21 strain's plasmid (Figure 3G ; Figure S12 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that the antimicrobial activity of the imidazolium group is related to the presence of the hydroxyethyl chain and the methyl group in the imidazolium ring structure [ 48 ]. Conversely, the potential electrostatic interaction between the imidazolium cations and the negatively charged cell wall is the main antimicrobial force [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, K. pneumoniae HCD1 utilizes OMVs as a sophisticated tool for survival and resistance, potentially spreading resistance within bacterial communities. It harbors genes for three beta-lactamases, including the carbapenemase KPC-2, placing it among highly resistant strains [ 109 ]. In another case, Haemophilus influenzae ( H. influenzae ), produces β-lactamase and packages it into vesicles.…”
Section: Example Of a Bacterial Ev Responsible For Antibiotic Resistancementioning
confidence: 99%